Protocol for automated tracking and quantification of adult zebrafish anxiety behavior using ZebraTrack - Atanu Pramanik; Shubham Nema; Yogesh Bhargava; Anamika Bhargava (STAR Protocols)
Summary: The open-field tank test is a well-validated technique for evaluating anxiety behavior in vertebrate animal models. However, manual behavioral analysis can be subjective and time consuming. Here, we present a protocol using ZebraTrack, an open-source ImageJ-based approach for distraction-free swimming video acquisition and automated tracking of adult zebrafish. We detail steps for mathematical calculations on 2D coordinates to extract various behavioral endpoints for anxiety-behavioral evaluation.For complete details on the use and execution of this protocol, please refer to Nema et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.